An investigation of the neurobiological mechanisms involved in the control of operant behaviour by reinforcers: quantitative studies using the progressive-ratio schedule - Olarte-Sánchez, Cristian Manuel (2012)
This thesis describes a series of experiments investigating the neural underpinnings of the ‘efficacy’ or ‘value’ of food reinforcers in the control of operant behaviour. A number of methods have been devised for measuring reinforcer value. The experiments described in this thesis employed the progressive-ratio schedule, in which the number of responses required to obtain a reinforcer is progressively increased with each successive reinforcer. The performance of rats on this schedule was analysed using a quantitative model of schedule-controlled behaviour, Killeen’s (1994) ‘Mathematical Principles of Reinforcement’ (MPR) model. An advantage of this approach is that MPR provides a theoretical basis for discriminating between the effects of interventions on ‘motivational’ and ‘motor’ aspects of operant behaviour. According to MPR, schedule-controlled behaviour may be characterized by an ‘activation’ parameter, a, which measures the reinforcer efficacy or value, a ‘response time’ parameter, δ, which measures the minimum inter-response time, and a ‘coupling’ parameter’ β which expresses the weight in short-term memory assigned to the most recent response.